2004
DOI: 10.1097/01.ta.0000093366.98819.fe
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Low Temperature on Shear-Induced Platelet Aggregation and Activation

Abstract: We found that platelets are hyper-reactive to fluid shear stress at temperatures of 24, 32, and 35 degrees C as compared with at 37 degrees C. The hyperreactivity results in heightened aggregation through a platelet-activation independent mechanism. The enhanced platelet aggregation parallels with increased whole blood viscosity at these temperatures, suggesting that enhanced mechanical cross-linking may be responsible for the enhanced platelet aggregation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
40
0
3

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 62 publications
(43 citation statements)
references
References 33 publications
0
40
0
3
Order By: Relevance
“…10 Small amounts of thrombin generated by contact-activation 11 or cold-activation of plasma activate factor V or factor VIII, accelerating both extrinsic and intrinsic coagulation [12][13][14] and activating platelets. [15][16][17] The phenomenon of cold-activation of plasma has been known for some decades, [18][19][20][21] but the exact thrombin amount generated in cold-activated recalcified plasma was not quantified. The present sensitive INCA technique allows the measurement of lowgrade contact activation of frozen/thawed plasma.…”
mentioning
confidence: 99%
“…10 Small amounts of thrombin generated by contact-activation 11 or cold-activation of plasma activate factor V or factor VIII, accelerating both extrinsic and intrinsic coagulation [12][13][14] and activating platelets. [15][16][17] The phenomenon of cold-activation of plasma has been known for some decades, [18][19][20][21] but the exact thrombin amount generated in cold-activated recalcified plasma was not quantified. The present sensitive INCA technique allows the measurement of lowgrade contact activation of frozen/thawed plasma.…”
mentioning
confidence: 99%
“…However, other investigators have reported the opposite, that refrigeration (< 21 days) retards the release of α-granule contents such as β-thromboglobulin [12,39,40]. Refrigerated platelets spontaneously form aggregates [41,42], respond better to agonists than room temperature platelets [11,[43][44][45][46][47][48][49][50][51], and adhere better to von Willebrand factor (vWf) under shear stress [52,53]. Furthermore, a recent study shows that systemic hypothermia of 31-34 °C in mice accelerates thrombus formation in arterioles and venules [43], indicating that exposure to temperatures below the physiological norm may activate platelets in vivo.…”
Section: Room Temperature Versus Refrigerated Storagementioning
confidence: 99%
“…Shivering also raises intracranial pressure (ICP) and requires the use of several pharmacological agents to inhibit these efects along with skin warming to address physical discomfort [20,21]. Another side efect of wholebody cooling is the risk of shear-induced platelet aggregation, which can develop as blood viscosity increases at low temperatures [22]. Even a minor amount of coagulation can cause a blockage of the microcirculation of the brain and heart, which ironically creates the exact problem that hypothermia atempts to treat [21].…”
Section: Systemic Hypothermiamentioning
confidence: 99%